Youth sexualities and sensibilities in the nightclubs of Lima - Loayza, Jerjes (2018)
Youths come across a number of problem being the aspect of sexuality where there are major and complex dimensions of interaction, referring to a simultaneous sexuality and characterized by various rituals that are expressed through dance and courtship between strangers in reserved spaces, supposedly for seniors: nightclubs visited by minors between 15 and 18 years old. Also, by young women, there will be a desire to experience in constant conflict with the values that define certain behavior especially towards women. It is concluded that the depth of the problem about youth sexuality is much more diverse and complex than is often recognized, being the study of bodies and the main emotions theoretical tool to introduce such issues of social, economic and political interest.